2013
DOI: 10.1016/j.matchemphys.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and strong ternary blends of poly(vinyl chloride), poly(butylene adipate) and nanoparticle-plasticizers

Abstract: h i g h l i g h t s g r a p h i c a l a b s t r a c t < Ternary blends of PVC, poly(-butylene adipate) (PBA) and nanofillers were prepared. < PBA plasticizer was grafted on surface of nanofillers. < Simultaneous up to 100% increase in stress and strain at break was obtained. a r t i c l e i n f o b s t r a c tMultiple property enhancement was achieved for ternary blends of PVC, poly(butylene adipate) (PBA) plasticizer and PBA-grafted nanofillers as compared to ternary blends with untreated nanofillers. The bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…PVC/nanoclay composites with a variety of polymers and plasticizers have been extensively studied by various research groups. [26][27][28][29][30][31][32][33] Kalendova et al [34] have prepared PVC/nanoclay composites with enhanced barrier properties but with slight reduction in plasticizer migration properties for various advanced packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…PVC/nanoclay composites with a variety of polymers and plasticizers have been extensively studied by various research groups. [26][27][28][29][30][31][32][33] Kalendova et al [34] have prepared PVC/nanoclay composites with enhanced barrier properties but with slight reduction in plasticizer migration properties for various advanced packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…HNTs are multi-walled inorganic materials that possess a unique combination of large aspect ratio (typically ca. 10e50), high mechanical strength, natural availability and good biocompatibility [13,14]. Similar to other nanofillers, fine dispersion throughout the polymer matrix and strong adhesion to the polymer are two keys in achieving HNT-supplemented nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Among various nanoparticles, silica (SiO 2 ) nanoparticles exhibited unique properties such as availability, low cost, well‐known chemistry and active hydroxyl groups that make this nanoparticle suitable for functionalization . Applying SiO 2 nanoparticles in polymer matrix improves its mechanical and thermal properties which make this nanoparticle desirable in many studies . In addition, previous studies showed that using SiO 2 as filler in nanocomposites has been led to enhancement mechanical properties in comparison to the polymers with the same structure.…”
Section: Introductionmentioning
confidence: 99%